Facile synthesis of graphene oxide from graphite rods of recycled batteries by solution plasma exfoliation for removing Pb from water. Issue 67 (12th November 2020) - Van Hao, Nguyen; Van Dang, Nguyen; Tung, Do Hoang; Tan, Pham The; Van Tu, Nguyen; Van Trinh, Pham
Abstract : Facile synthesis of graphene oxide from graphite rods of recycled batteries by solution plasma exfoliation for removing Pb from water. Abstract : We herein present a simple, fast, efficient and environmentally friendly technique to prepare graphene oxide (GO) from graphite rods of recycled batteries by using solution plasma exfoliated techniques at atmospheric pressure. The prepared GO with an average 3 nm-thickness and 1.5 μm-length, having large surface area and high porosity, has been used to remove Pb(ii ) ions from the water. The obtained results indicated that the adsorption of Pb(ii ) onto GO depends on pH, contact time, temperature and initial concentration of Pb(ii ). The maximum adsorption capacity of Pb(ii ) onto GO determined from the Langmuir model (with a high R 2 value of 0.9913) was 180.1 mg g −1 at room temperature. A removal efficiency of ∼96.6% was obtained after 40 min. Calculations of thermodynamic parameters (Δ G °, Δ H ° và Δ S °) show the adsorption of Pb(ii ) ions on the GO surface is spontaneous and intrinsically heat-absorbing. The potential mechanism can be suggested here to be the interaction of the π–π* bonding electrons and Pb(ii ) as well as the electrostatic attraction between Pb(ii ) and the oxygen-containing functional groups on GO.